Managerial Risk-Taking Incentive and Firm Innovation: Evidence from FAS 123R - Mao, Connie X.; Zhang, Chi (Journal of Financial and Quantitative Analysis, 2018)
We investigate how chief executive officers’ (CEOs) risk incentive (VEGA) affects firm innovation. To establish causality, we exploit compensation changes instigated by the FAS 123R accounting regulation in 2005 that mandated stock option expensing at fair values. Our identification tests indicate a positive and causal effect of CEOs’ VEGA on innovation activities. Furthermore, dampened managerial risk-taking incentive after the implementation of FAS 123R leads to a significant reduction in innovation related to firms’ core business and explorative inventions. It implies that managers diversify their innovation portfolios and decrease explorative inventions to curtail business risk when their risk-taking incentive is reduced.